(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
App Annie’s Data in 2021 lists Indonesia as the world most mobile-oriented region. One of the frequent accessed applications by smartphone is Shopee. This study aims to determine the influence of distribution, promotion and service-quality variable on purchasing decision at Shopee during the covid-19 pandemic partially or simultaneously. The research method used quantitative. The data collection used questionnaire. The sample was 100 Shopee consumers. The results showed that distribution did not have partial effect on purchasing decisions with a value of 0.696, promotion had a partial effect on purchasing decisions with a value of sig. 0.000, and service quality had a partial effect on purchasing decisions with a sig value. is 0.000. Among the three variables, promotion was the most dominant variable on purchasing decision.